Implementation of the regulations of the board of directors of TVRI public agency on Non-Civil Servant in public television broadcasting agency in Indonesia - Erasmus Nagi Noi; Alo Liliweri; Lenny N. Tammunu (Annals of Management and Organization Research)
Purpose: This research aims to analyze the implementation of the regulation of the board of directors of the TVRI public broadcasting institution regarding non-civil servants (Study at the Indonesian Television Public Broadcasting Institute (TVRI), East Nusa Tenggara Station. Research methodology: In this study, the authors used an interpretive research paradigm. The interpretive approach aims to understand the "world of human experience". In this study, the total population was 110 people consisting of 27 non-civil servants and 83 civil servants. Furthermore, purposively, the researcher selected 11 people as informants with details of 1 Head of the Office as Key Informants and 10 non-civil servants as Ordinary Informants Results: The conclusions of this study can be grouped into four aspects, namely actors, organizations, procedures, and techniques. Limitations: this research only analyzes the implementation of policies on the development of Indonesian migrant workers' families in the field of economic empowerment in Kupang city. Contribution: This research becomes scientific information for public administration science. Keywords: Regulations, Implementation, Broadcasting agency, Non-Civil Servant